Tổng hợp perovskit La0,8Ce0,2 MnO3 ở nhiệt độ thấp bằng phương pháp đốt cháy gel PVA - Đại, Lưu Minh; Dũng, Nguyễn Xuân (Vietnam Journal of Chemistry, 2012)
La0.8Ce0.2MnO3 has been synthesised at temperatue (650oC) by the combustion of gel prepared from polyvinyl alcohol (PVA) and metal nitrates. La0.8Ce0.2MnO3 characterization is examined by X-ray diffraction (XRD), thermogravimetric and differential thermal analysis (TG-DTA), Field Emission Electron Microscopy (FESEM) and BET(Brunaure-Emmet-Teller) measurements. The obtained  sample under optional preparative conditions  has nano scale with specific square area of 21.1 m2/g.